Analisis Gen Selubung Protein Chilli Veinal Mottle Potyvirus dari Beberapa Daerah di Indonesia - Ifa Manzila; Sri H. Hidayat; Ika Mariska; Sriani Sujiprihati (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2012)
Variation on symptoms and virulence wasobserved on different isolates of ChiVMV collected fromWest Java, Central Java, East Java, South Kalimantan, WestSumatera and Central Aceh. Research was conducted tostudy genetic variation of six ChiVMV isolates based onsequence analysis of coat protein (CP) gene and aminoacid. Sequence analysis of CP gene showed 87% to 99%homology among the six isolates with level of variationranging from 0.02% to 1.48%. Sequence analysis of aminoacid derived from CP gene showed 85% to 99% homology.Further analysis on amino acid motives of CP gene indicatedmutation of octapeptide motif, i.eLSGQVQPQSRQSEMETEVPQVR on ChiVMV CKB andRMETFGLDGRVGTQEEDTERHT on other ChiVMV isolates.Other differences was observed on amino acid number 61and 84 i.e. deletion of MET and mutation of GG to KV onChiVMV BL and KR. Phyllogenetic analysis based onnucleotide and amino acid sequence showed that sixisolates of ChiVMV can be differentiated into three groups.ChiVMV KR and BL were in the same group with ChiVMVPataruman (GeneBank No. access DQ854961), ChiVMV CKBwas in the same group with ChiVMV Cikabayan 2(GeneBank No. access DQ854960), and ChiVMV TD, ChiVMVNI and GB ChiVMV were in the same group with ChiVMVTaiwan (GeneBank No. access DQ854948). Analysis of CPgene confirmed the occurrence of genetic variation amongChiVMV isolates although symptom variation is weak.